Le modèle québécois : un horizon théorique pour la recherche, une porte d’entrée pour un projet de société ? - Benoît Lévesque (Revue Interventions Économiques)
There is a Quebecois model of development in emergence of partenarial type. This model is different as well from the keynesian model and fordist of the « Révolution Tranquille » as the neoliberalism. On the other hand, this model does not still possess solid bases, because insufficiently institutionalized. The possible features of this new configuration were identified by the works of CRISES about the social innovations of both last introduced decades. These innovations result from organized social actors within the industrial companies, within the certain trade services and within the social economy Furthermore, contrary to the fact that some people think, there is another way of thinking of the renewal of the model of development. A mode based on the solidarity which gives more place to the partnership and to the civil society would be the foundation of this renewal.